Design of CMOS three-stage amplifiers for near-to-minimum settling-time. (January 2021) - Giustolisi, Gianluca; Palumbo, Gaetano
Abstract: In this paper, we provide a new procedure that allows to design a generic three-stage amplifier from settling-time specifications. The procedure analyze the settling-time of pure two- or three-pole amplifiers (i.e., with no zeros) and extends the results to a generic amplifier that includes one or two zeros even placed in the right-half plane. The validity of the proposed approach is demonstrated through a design example of a three-stage CMOS amplifier suitable for switched-capacitor applications.